Painting of Parshvanath Tirthankara - Temples of India Project Team (Jio Institute, 2024)
Painting of Parshvanath Tirthankara on the wall flanking the side entrance doorways of the mandapa (pillared hall) of the Bhandasar Temple. Standing on a hooded snake, Parshvanath is shown emerging from the mouth of the snake amidst water. He has four attendants on either side The inscription reads– ‘megh malinapa sarga parshvanathji’.